Copper-Catalyzed Cross-Coupling of Arylacetylenes with Bromodifluoroacetamides - Hu, Guo-Qin; Yao, Li-Wei; Gui, Shu-Sheng; Geng, Chuang; Zhang, Wen-Yan; Liu, Jing-Hui; Zhao, Bin (Synlett, 2022)
A copper-catalyzed radical difluoroalkylation of arylacetylenes with bromodifluoroamides has been developed. The reaction exhibits good functional group tolerance and allows access to a variety of substituted α-alkynyl-α,α-difluoroacetamides in moderate to good yields. The potential for scale-up reaction and products derivatization also makes this method attractive for practical applications. Preliminary mechanistic studies suggest that a radical reaction pathway might be involved in the catalytic system.
Keywords: copper catalysis; arylacetylenes; bromodifluoroacetamides; cross-coupling; difluoroalkylation